2014
DOI: 10.1021/am405418g
|View full text |Cite
|
Sign up to set email alerts
|

Nanofiber Scaffolds with Gradients in Mineral Content for Spatial Control of Osteogenesis

Abstract: Reattachment of tendon to bone has been a challenge in orthopedic surgery. The disparate mechanical properties of the two tissues make it difficult to achieve direct surgical repair of the tendon-to-bone insertion. Healing after surgical repair typically does not regenerate the natural attachment, a complex tissue that connects tendon and bone across a gradient in both mineral content and cell phenotypes. To facilitate the regeneration of the attachment, our groups have developed a nanofiber-based scaffold wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
137
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(140 citation statements)
references
References 61 publications
3
137
0
Order By: Relevance
“…Commonly used biomaterials for bone include calcium phosphate ceramics (in particular hydroxyhapatite (HA) [28][29][30] and β-tricalciumphosphate (β-TCP) [28,[31][32][33]), bioactive glasses (mainly silicate-based 45S5 Bioglass ® [34,35]), natural polymers (such as alginate [36], silk [10,29,37] and collagen [38][39][40][41][42]) and synthetic polymers (particularly poly(ɛ-caprolactone) (PCL) [31,32,[43][44][45], poly-L-lactic acid (PLLA) [33], polyglycolic acid (PGA) [45] and polylactid-co-glycolid acid (PLGA) [46,47]) (table 2).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Commonly used biomaterials for bone include calcium phosphate ceramics (in particular hydroxyhapatite (HA) [28][29][30] and β-tricalciumphosphate (β-TCP) [28,[31][32][33]), bioactive glasses (mainly silicate-based 45S5 Bioglass ® [34,35]), natural polymers (such as alginate [36], silk [10,29,37] and collagen [38][39][40][41][42]) and synthetic polymers (particularly poly(ɛ-caprolactone) (PCL) [31,32,[43][44][45], poly-L-lactic acid (PLLA) [33], polyglycolic acid (PGA) [45] and polylactid-co-glycolid acid (PLGA) [46,47]) (table 2).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…One study highlighted the use of fibrous scaffolds in conjunction with a mineralization pattern to promote osteogenesis. [103] To further this, rotator cuff fibroblasts could be co-cultured to create a bone-tendon transitional environment, which could potentially regenerate the interfacial region. In a similar study, a mineralized graded scaffold formed on plasma treated PLGA and gelatin coated PCL electrospun fibers was investigated (Figure 5a,b).…”
Section: Nanoengineered Bone-tendon Interfacementioning
confidence: 99%
“…[104] A recent study, however, indicated that calcium phosphates may inhibit osteogenic differentiation due to their low crystallinity and high rate of dissolution. [103] The native tissue architecture of the bone-tendon interface exhibits a change in fiber alignment;…”
Section: Nanoengineered Bone-tendon Interfacementioning
confidence: 99%
“…tendon enthesis). Mineralization of collagen can influence cell attachment, proliferation and differentiation [23]. Presentation of mineral or increased stiffness to mesenchymal stem cells, for example, has the capacity to stimulate differentiation into an osteoblast lineage [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Mineralization of collagen can influence cell attachment, proliferation and differentiation [23]. Presentation of mineral or increased stiffness to mesenchymal stem cells, for example, has the capacity to stimulate differentiation into an osteoblast lineage [22,23]. Controlling mineral concentration spatially can therefore be useful for engineering tissues such as the tendon enthesis, which exhibits spatial gradients in mineral content and cellular phenotypes (tendon fibroblast, fibrochondrocyte, osteoblast/osteocyte).…”
Section: Discussionmentioning
confidence: 99%